Hodgkin's lymphoma associated T‐cells exhibit a transcription factor profile consistent with distinct lymphoid compartments - Atayar, Çiğdem (BMJ Group, 2007)
BACKGROUND: Hodgkin's lymphoma (HL) is characterised by an ineffective immune response that is predominantly mediated by CD4(+) T‐cells. AIMS: To analyse the expression of the key regulatory T‐cell transcription factors (TFs) in the T‐cells of HL involved tissues in order to assess the nature of the T(H) immune response in HL. METHODS AND RESULTS: By immunohistochemistry, GATA3 was strongly and T‐bet exclusively expressed in a subset of interfollicular lymphocytes in the reactive lymphoid tissues. In classical HL (CHL), which is generally located in the interfollicular zones, a predominance of T‐bet(+) T‐cells and lesser amounts of GATA3(+) and c‐Maf(+) T‐cells was found, concordant with the pattern of the normal interfollicular compartment. In reactive lymphoid tissues, c‐Maf was observed mostly in T‐lymphocytes within the germinal centres (GCs). Nodular lymphocyte predominance type of Hodgkin's lymphoma (NLPHL) and progressively transformed germinal centres cases, showed a majority of c‐Maf(+) T‐cells, consistent with the pattern in normal GCs. NLPHL cases uniformly showed c‐Maf(+)/CD57(+) T‐cell rosettes around the neoplastic cells; these rosettes were absent in “paragranuloma‐type” T‐cell/histiocyte rich B‐cell lymphoma. CONCLUSIONS: T‐cell TF expression profiles of the reactive T‐cells in both subtypes of HL are in accordance with the expression profile observed in the distinct lymphoid compartments.